PENGGUNAAN MIND MAP DALAM MATA KULIAH ANATOMI FISIOLOGI MANUSIA SEBAGAI INTEGRASI BERBAGAI KONSEP UNTUK MENINGKATKAN HASIL BELAJAR MAHASISWA TA 2014/2015 - Nurkhairo Hidayati (Florea : Jurnal Biologi dan Pembelajarannya, 2015)
Human anatomy and physiology course has a variety of interrelated or integrate concepts and causal relationship, so that the concepts easier to understand student learning process is done using a mind map. The role of the mind map is very important because it helps the students categorize the material in accordance with the idea that it is easier to understand. Mind map is a way of noting a fun, easy way to absorb and release information and new ideas. Mind map using sign or symbol which is equipped with a color. Signs or symbols that are used as well as color influence strengthening student understanding and memory. Each concept can be expressed with one word idea and visualized with a symbol or image. This research aims to improve student learning outcomes in Human Anatomy Physiology using mind map. This research is a classroom action research that begins with: 1) planning action, 2) implementation, 3) observation, 4) reflection. The results showed an increase in student learning outcomes. The first cycle, the average student learning outcomes is 66, 32. The second cycle, the average student learning outcomes 70,35 and increased again in third cycle to 76.79. Based on the results concluded that the use of mind mapping can improve learning outcomes of students in the subject of Human Physiology Anatomy.